The Experience of Witnessing Patients' Trauma and Suffering Among Acute Care Nurses - Walsh, Mary E.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2011)
A large body of research provides evidence of workplace injuries to those in the nursing profession. Research on workplace stress and burnout among medical professionals is also well known; however, the profession of acute care nursing has not been examined with regards to work-related stress. This qualitative study focused on acute care nurses’ workplace stress, as 5 acute care nurses described experiences related to witnessing patients’ trauma and suffering. Through the use of phenomenological analysis, five main themes emerged from the interviews, revealing a more in-depth understanding of nurses’ experiences in acute care settings. These themes were (a) shock and prolonged witnessing of suffering, (b) long-term effects, (c) distancing as a coping strategy, (d) feelings of guilt and helplessness, and (e) dissonance in core beliefs about self. The results are discussed in terms of coping strategies and recommendations for counsellors working with health care professionals.